Utilization of bioethanol generated from papaw peel waste for hand sanitizer production - Amanullah, A.; Kapilan, R. (Research gate, 2021)
Hands are the primary mode for the spread of microbes. For infection control, the first-line of defense as well as personal hygiene, are mandatory. Hand sanitizers that contain ethanol as the main constituent are used to kill a broad range of microbes. Demand for petroleum-derived ethanol is increasing with the COVID-19 outbreak and primary suppliers are searching for alternatives to overcome this problem. Objective of this study is to produce bioethanol from ripen papaw peel waste using Saccharomyces cerevisiae and to determine the potential utilization of bioethanol generated from papaw peel waste for a pilot study of which the end aim is hand sanitizer production. The blended ripened papaw (Carica papaya) fruit peel (100g/L) was inoculated with the S. cerevisiae (2g/L) in a fermentation medium that contains 10 g/L yeast extract, 10 g/L KH2PO4, 2 g/L (NH4)2SO4 and 0.5 g/L MgSO4•7H2O and allowed to ferment for 6-36 hours at room temperature. The bioethanol yield obtained after 12 hours, was 0.6% (V/V). The fermentation conditions were optimized by changing one factor at a time, while keeping the other variables constant. Significantly higher bioethanol yield (6.2 times, 3.7% V/V [p<0.05]) was obtained from papaya peels at the optimized conditions of 12 hours of incubation period, 5:1 ratio between air space and fermentation solution, 5g/L of yeast inoculum, 15g/100ml of papaw fruit peel, 1g/100ml of soybean powder as nitrogen source, 60ml/100ml of diluted sulfuric acid at pH 5. When the agar well diffusion assay was performed against pathogenic bacteria such as Escherichia coli, Staphylococcus aureus, Bacillus spp. and Pseudomonas spp, all the bacterial strains showed an inhibition zone, i.e., they were sensitive for the bioethanol extract.
Keywords: Saccharomyces cerevisiae; Bioethanol; Papaw peel waste; Soybean